Analysis of Community Social Economic Resilience Based on Coastal and Marine Natural Resources - Dhiana Puspitawati; Moh. Fadli; Moelyadi Moelyadi; Adi Kusumaningrum; Supriyadi Supriyadi; Mentari Puspa Wardani; Asyifa Anandya (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
Ecotourism's dependence on climate resources makes it one of the industries considered to be the most vulnerable. This study aims to analyze the socio-economic conditions of vulnerability and resilience of coastal and marine natural resources related to ecotourism development. Data analysis used descriptive qualitative analysis to identify perceptions of disaster characteristics and impacts and climate variability, as well as quantitative descriptive analysis to calculate changes in the household income of the Tamban Beach community and the level of resilience and vulnerability using the Livelihood Vulnerability Index (LVI) method. The results show that the highest value of the main component is the ecology of 0.880, so it becomes the most vulnerable component. The factor with the highest value is the sensitivity, which is 0.475 and is the weakest. The LVI value in Tamban Beach is 0.311, indicating that community households in the area have a reasonably low vulnerability to coastal and marine resources in Tamban Beach. The household resilience level of the Tamban Beach community is mostly in the moderate category, as much as 45%. The Tamban Beach community needs to participate in seeking information on climate change actively weather forecasts together with related institutions.